Neoadjuvant FLOT versus SOX phase II randomized clinical trial for patients with locally advanced gastric cancer - Birendra Kumar Sah (Nature Portfolio, 2020)
Neoadjuvant FLOT regimen has shown promising results for the treatment of locally advanced gastric cancer, however SOX regimen remains the preferred chemotherapy in Eastern countries. Here the authors report that the two therapies result in similar outcomes, measured as clinical downstaging and pathological response, in a phase II randomized clinical trial.